Fast and Sensitive Method for Determination of Domoic Acid in Mussel Tissue - Elena Barbaro; Roberta Zangrando; Carlo Barbante; Andrea Gambaro (The Scientific World Journal)
Domoic acid (DA), a neurotoxic amino acid produced by diatoms, is the main cause of amnesic shellfish poisoning (ASP). In this work, we propose a very simple and fast analytical method to determine DA in mussel tissue. The method consists of two consecutive extractions and requires no purification steps, due to a reduction of the extraction of the interfering species and the application of very sensitive and selective HILIC-MS/MS method. The procedural method was validated through the estimation of trueness, extract yield, precision, detection, and quantification limits of analytical method. The sample preparation was also evaluated through qualitative and quantitative evaluations of the matrix effect. These evaluations were conducted both on the DA-free matrix spiked with known DA concentration and on the reference certified material (RCM). We developed a very selective LC-MS/MS method with a very low value of method detection limit (9 ng g−1) without cleanup steps.